The Effects of Professor Gender on the Post-Graduation Outcomes of Female Students - Hani Mansour; Daniel I. Rees; Bryson Rintala; Nathan Wozny (Institute of Labor Economics (IZA), 2018)
Although women earn approximately 50% of science, technology, engineering and math (STEM) bachelor's degrees, more than 70% of scientists and engineers are men. We explore a potential determinant of this STEM gender gap using newly collected data on the career trajectories of United States Air Force Academy students. Specifically, we examine the effects of being assigned female math and science professors on occupation and postgraduate education. We find that, among high-ability female students, being assigned a female professor leads to substantial increases in the probability of working in a STEM occupation and the probability of receiving a STEM master's degree.
Keywords: I20; J16; J24; 330; gender gap; STEM occupational choice; post-graduate education